Nanoliposome-Encapsulated Brinzolamide-hydropropyl-β-cyclodextrin Inclusion Complex: A Potential Therapeutic Ocular Drug-Delivery System - Wang, Fazhan; Bao, Xingting; Fang, Aiping; Li, Huili; Zhou, Yang; Liu, Yongmei; Jiang, Chunling; Wu, Jinhui; Song, Xiangrong (Frontiers in Pharmacology, 2018)
Abstract Novel ocular drug delivery systems (NODDS) remain to be explored to overcome the anatomical and physiological barriers of eyes. This study was to encapsulate brinzolamide (BRZ)-hydropropyl-β-cyclodextrin (HP-β-CD) inclusion complex (HP-β-CD/BRZ) into nanoliposomes and investigate its potential as one of NODDS to improve BRZ local glaucomatous therapeutic effect. HP-β-CD/BRZ was firstly prepared to enhance the solubility of poorly water-soluble BRZ. The HP-β-CD/BRZ loaded nanoliposomes (BCL) were subsequently constructed by thin-film dispersion method. After the optimization of the ratio of BRZ to HP-β-CD, the optimal BCL showed an average size of 82.29 ± 6.20 nm, ζ potential of -3.57 ± 0.46 mV and entrapment efficiency (EE) of 92.50 ± 2.10% with nearly spherical in shape. The X-ray diffraction (XRD) confirmed the formation of HP-β-CD/BRZ and BCL. The in vitro release study of BCL was evaluated using the dialysis technique, and BCL showed moderate sustained release. BCL (1 mg/mL BRZ) showed a 9.36 fold increase in the apparent permeability coefficient and had a sustained and enhanced intraocular pressure reduction efficacy when compared with the commercial available formulation (BRZ-Sus) (10 mg/mL BRZ). In conclusion, BCL might have a promising future as a novel ocular drug delivery system for glaucoma treatment. Keywords: brinzolamide, cyclodextrin, inclusion complex, nanoliposomes, intraocular pressure, ocular drug delivery